Depression Screening Scores and Allergy and Gastrointestinal Medication Use in Adolescents - Harris, Kari; Saikumar, Pavithra; Sunkoj, Yojana; Vancuren, Trista; Olufowote, Blessing; Dedeaux, Julian (Current Drug Safety, 2023)
Introduction: Between 2005 and 2014, the 12-month prevalence of major depressive episodes among adolescents aged 12 to 17 years increased from 8.5% to 11.3%. Adolescent-onset depression is related to increased risk for depression and suicidal attempts in adulthood. It is known that depression is an adverse effect among adults taking OAM; however, the effect of OAM on adolescents is unknown. Aim: The aim of this study was to describe the relationship between Patient Health Questionnaire 9- Modified (PHQ9-M) scores and OAM use among adolescents. Methods: This study included data abstracted from charts of adolescents aged 12 to 21 years who completed a Kansas Be Healthy wellness appointment at the KUSM-W Peds Clinic in 2017. Odds ratios were used to calculate the relationship between oral allergy medication and gastrointestinal medication use among adolescents and PHQ9-M scores. Results: Of the 425 adolescent charts analyzed, 22% (n=96) had positive PHQ9-M screens (a score of 10 or greater), and 13% (n=56) reported current use of allergy medication and/or GI medications. Adolescents taking oral allergy medication were 1.77 times more likely to have a positive PHQ9-M screen than those not taking oral allergy medication. Among adolescents on allergy medication, there was no difference in PHQ9- M scores based on the drug class (1st or 2ndgeneration antihistamine or Montelukast). Conclusion: Healthcare providers must diligently explore OAM/GI use with adolescents during clinical encounters and discuss possible adverse effects of OAM on mood.
Keywords: teens